A novel approach for the detection and exploration of joint coupling patterns in the lower limb kinetic chain - Deschamps, Kevin; Eerdekens, Maarten; Geentjens, Jurre; Santermans, Lieselot; Steurs, Lien; Dingenen, Bart; Thysen, Maarten; Staes, Filip (Gait & posture, 2018)
•Exploring joint coupling patterns within the lower limb kinetic chain.•Hierarchical clustering of cross-correlation coefficients.•Linking joint kinetics with kinematic joint coupling. A comprehensive perspective on foot and lower limb joint coupling is lacking since previous studies did not consider the multi-articular nature of the foot and lower limb neither accounted for biomechanical heterogeneity. The current manuscript describes a novel methodological process for detection and exploration of joint coupling patterns in the lower limb kinetic chain. The first stage of the methodological process encompasses the measurement of 3D joint kinematics of the foot and lower limb kinetic chain during dynamic activities. The second stage consists of selecting the kinematic waveforms of interest. In the third stage, cross-correlation coefficients are calculated across the selected one-dimensional continua of each subject. In the fourth stage, all cross-correlation coefficients per subject are used as input variable in a cluster algorithm. Algorithm specific qualitative metrics are subsequently considered to determine the most robust clustering. Finally, in the fifth stage the process of biomechanical interpretation is initiated and further exploration is recommended by triangulating with other biomechanical variables. A first clinical illustration of the novel method was provided using data of fourteen young elite athletes. Cross-correlation coefficients for each leg were calculated across continua of the pelvis, hip, knee, rear foot and midfoot. A hierarchical clustering approach stratified the coefficients into two distinct clusters which was mainly guided by the frontal plane knee kinematics. Both clustered differed significantly from each other with respect to their frontal plane ankle, knee and hip kinetics. The presented method seems to provide a valuable approach to gain insight into foot and lower joint coupling.